1974
DOI: 10.1002/jmor.1051430203
|View full text |Cite
|
Sign up to set email alerts
|

Myelin movements in mature mammalian peripheral nerve fibers

Abstract: Mature mouse and cat peripheral nerve fibers have been examined in vitro by time-lapse photography. Some Schmidt-Lanterman clefts which were open at the start closed later; others were seen to open and then to close, some of them more than once. The implications of these movements are considered, especially in regard to the question of the passage of materials from the endoneurial connective tissue spaces to the axon.Myelin movements other than those occurring at the Schmidt-Lanterman clefts consisted primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…There is a balance between the processes of aggregation and splitting of myelin layers, especially in the paranode -node -paranode regions, which together with the Schmidt -Lanterman incisures are the most labile and complex regions of the fibre [17]. Prolonged repetitive excitation leads to changes in the myelin structure even in normal fibres.…”
Section: Activity-dependent Changes In Myelin Structurementioning
confidence: 99%
“…There is a balance between the processes of aggregation and splitting of myelin layers, especially in the paranode -node -paranode regions, which together with the Schmidt -Lanterman incisures are the most labile and complex regions of the fibre [17]. Prolonged repetitive excitation leads to changes in the myelin structure even in normal fibres.…”
Section: Activity-dependent Changes In Myelin Structurementioning
confidence: 99%
“…While transport of proteins from a neuronal cell body to a peripheral axonal site may occur over a distance of several feet in large mammals, the maximum distance in transporting materials from a Schwann cell body to a site near the axon is only -8,000 km for a 15 p,m myelinated fibre when the longest route is used of looping around 200 concentric rings of myelin lamellae via the Schmidt Lanterman incisures. Time-lapse photography has shown pulsating movements along these incisures in adult nerves (Gitlin and Singer, 1974). Transport of RNA to maintain protein synthesis in the distal processes of a Schwann cell takes place at an extremely slow rate, namely, on the order of 0.1 mm per day along the outermost cytoplasm of an internode (Gould and Mattingly, 1990).…”
Section: Schwann Cell To Axon Transfermentioning
confidence: 99%
“…Biological membranes are generally regarded as being fluid in nature with constituent proteins and lipids able to move relative to one another in the plane of the membrane (Singer & Nicolson, 1972). Fluidity in the myelin sheath has been demonstrated in vitro by Matus, de Petris & Raff (1973), who showed that concanavalin A receptors, glycoproteins evenly dispersed in the intraperiod lines of myelin, were redistributed into clusters by addition ofcross-linking antibodies, and by Gitlin & Singer (1974), who observed development and regression of indentations in the myelin sheath and opening and closure of Schmidt-Lanterman incisures. Present observations indicate that myelin components may undergo rapid reversible redistribution in vivo without loss of structural integrity.…”
Section: Discussionmentioning
confidence: 99%